2016
DOI: 10.1186/s40064-016-1881-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficient conversion of xylose to ethanol by stress-tolerant Kluyveromyces marxianus BUNL-21

Abstract: The fermentation ability of thermotolerant Kluyveromyces marxianus BUNL-21 isolated in Laos was investigated. Comparison with thermotolerant K. marxianus DMKU3-1042 as one of the most thermotolerant yeasts isolated previously revealed that the strain possesses stronger ability for conversion of xylose to ethanol, resistance to 2-deoxyglucose in the case of pentose, and tolerance to various stresses including high temperature and hydrogen peroxide. K. marxianus BUNL-21 was found to have ethanol fermentation act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…K. marxianus DBKKUY-103, that was recently isolated, achieved the maximum ethanol concentration of 83.5 g/L, corresponding to 96.6% of the theoretical yield [47]. Nitiyon et al [37] reported that K. marxianus BUNL-21 is a highly competent yeast for high-temperature ethanol fermentation with lignocellulosic biomass. When compared with the strain DMKU 3-1042, the strain BUNL-21 had stronger ability for conversion of xylose to ethanol and tolerance to various stresses including high temperature and hydrogen peroxide.…”
Section: Various Ethanologenic Thermotolerant Yeasts and Their Characmentioning
confidence: 99%
See 3 more Smart Citations
“…K. marxianus DBKKUY-103, that was recently isolated, achieved the maximum ethanol concentration of 83.5 g/L, corresponding to 96.6% of the theoretical yield [47]. Nitiyon et al [37] reported that K. marxianus BUNL-21 is a highly competent yeast for high-temperature ethanol fermentation with lignocellulosic biomass. When compared with the strain DMKU 3-1042, the strain BUNL-21 had stronger ability for conversion of xylose to ethanol and tolerance to various stresses including high temperature and hydrogen peroxide.…”
Section: Various Ethanologenic Thermotolerant Yeasts and Their Characmentioning
confidence: 99%
“…Ethanol production at high temperatures by thermotolerant yeasts has earned much interest due to several advantages as described above [38]. There are several ethanologenic yeasts that have been characterized and classified as thermotolerant yeasts such as K. marxianus [31,37,47], P. kudriavzevii (formally known as I. orientalis) [20,48,49,65,66], Hansenula polymorpha [67], and some strains of S. cerevisiae [21,52,[68][69][70]. However, for cost-effective and efficient ethanol production, not only thermotolerance but also a broad spectrum in sugar assimilation and fermentation capability is beneficial for the conversion of a variety of raw materials containing various sugars to ethanol, especially xylose, which is the most common pentose sugar and the second most abundant after glucose in lignocellulosic biomass and algal biomass [71,72].…”
Section: Utilization Of Various Sugars In Thermotolerant Yeastsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding confirmed that the strains could not utilize xylose. According to Moysés et al (2016) and Nitiyon et al (2016), the present of high concentration of xylose in the medium causes the osmotic stress for yeast strain.…”
Section: The Characteristic Of Yeasts In Various Inhibitors Compoundsmentioning
confidence: 99%